A Morphological Study on the Carbon Particles from Wood Fiber Waste via Hydrothermal Carbonization Process - Saidatul Shima, Jamari; Howse, Jonathan R.; Azlinna, A. Bakar (IACSIT Press, 2013)
Wood fiber waste is abundantly produced from the medium density wood fiber industry. The production of carbon from biomass is having more intention from the researcher due to the application. In this research, the conversion of biomass from wood fiber waste into carbon particle via hydrothermal carbonization (HTC) process is chosen. In this experiment, wood fiber and water were added in a pressure vessel and heated up to temperature between 200 – 220°C for 4 hours. Analyses were carried out using Elemental Analyzer, TGA, FTIR and FESEM for the characterization phase. The carbon value recorded an improvement as the O/C ratio of raw material is higher than the HTC products. The surface morphology obtained from FESEM showed pores on the surface of the HTC product suggesting a processing route to complicated carbon based structures. It can be concluded that both processes is practicable method to convert biomass into value added product.